Influence of Pre-Slaughter Environmental Temperature on Meat Quality of Crossbred Pigs of Andhra Pradesh: doi: 10.5958/2581-6616.2021.00010.4 - Mallika, E. Naga; Rao, V. Giridhara; Prasanna, M.; Sree, A. Shilpa; Gowtham, P.; Rao , B. Eswara (Journal of Meat Science, 2021)
This study aimed to investigate the effect of high environmental temperature on meat quality traits of crossbred pigs  brought for slaughter to the experimental abattoir of the Department of Livestock Products Technology, NTR College  of Veterinary Science, Sri Venkateswara Veterinary University, Andhra Pradesh, India. High pre-slaughter environmental  temperature significantly (P
Keywords: Pre-Slaughter care; Environmental temperature; Meat quality; Crossbred pigs; Meat parameters